Pengaruh Audit Tenure, Dewan Independen, dan Independensi Audit terhadap Kualitas Audit dengan Kepemilikan Institusional sebagai Pemoderasi - Trisnawati, Trisnawati; Jefriyanto, Jefriyanto (Jurnal Eksplorasi Akuntansi, 2024)
The purpose of this study is to examine how audit independence, audit tenure, and independent boards affect audit quality when institutional ownership is moderated. This study employs quantitative methods. The firm's annual reports, which were retrieved from the website of the Indonesia Stock Exchange and the company in question, served as the study's source of data. Using the purposive sampling technique, this study collected 117 samples between 2020 and 2022 from 39 manufacturing enterprises in the food and beverage and textile and garment subsectors. This study use the logistic regression analysis approach to test the hypothesis and moderated regression analysis to evaluate the moderation hypothesis. The study's findings show that institutional ownership has a moderating influence on audit quality and that audit tenure, audit independence, and independent boards have no effect.